User-friendly streets for a walkable, liveable and sustainable environment: a review - Khalaf, Omar Abdulwahhab; Nor Haslina Ja`afar, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Streets are an important element of freely accessible public space and constitute the most significant manifestation of the public domain. They exist to cater for the social and leisure requirements of the public and have a positive association with economic development, public physical well-being and help establish an environment of communal bonding. It is therefore crucial that streets are friendly to all users, a public space which provides a liveable environment for pedestrians with a walkable environment that is inviting, safe, aesthetically pleasing, and equipped with sufficient pedestrian amenities. Thus, this paper aims to examine the physical design features and characteristics of user- friendly streets that contribute to a evil able environment. This review of the literature on liveability and user- friendly streets indicates that many factors influence the degree of liveliness and form and finds that the physical design and characteristics like Proportion and dimension, Sense of enclosure, Scale of street, Transparency, Unity and Quality of View. Also finds the qualities of a user-friendly street such as, Comfort and convenient, Safety and security, and Accessibility and linkages. All factors based on the purpose of physical forms and appearances, socio-economic and characteristics of both users and the residents. As such, a well-designed street environment is essential with the streets as ‘public space’ which can enhance their liveable environments in advance.